2014
DOI: 10.1016/j.parkreldis.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic nucleus deep brain stimulation in early stage Parkinson's disease

Abstract: Background Deep brain stimulation (DBS) is an effective and approved therapy for advanced Parkinson’s disease (PD), and a recent study suggests efficacy in mid-stage disease. This manuscript reports the results of a pilot trial investigating preliminary safety and tolerability of DBS in early PD. Methods Thirty subjects with idiopathic PD (Hoehn & Yahr Stage II off medication), age 50–75, on medication ≥ 6 months but < 4 years, and without motor fluctuations or dyskinesias were randomized to optimal drug the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 22 publications
(38 reference statements)
3
111
0
3
Order By: Relevance
“…The number of trials for each identifiable therapeutic intervention category was 3 for dopaminergic agonists [17][18][19], 2 for cannabinoids and opioids [20,21], 3 for surgical methods [22][23][24], 4 for electrical or Chinese therapies [25][26][27][28], 2 for pardoprunox [29,30], 2 for safinamide [16], 1 for catechol-O-methyltransferase (COMT) inhibitors [31], 1 for multidisciplinary team care [32], and 7 for miscellaneous therapies. Miscellaneous therapies included hydrotherapy [33,34], massage therapy [35], gym training [36], mindfulness therapy [37], vibration therapy [38], and power yoga [39] (Table 1, with further intervention details in Appendix 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of trials for each identifiable therapeutic intervention category was 3 for dopaminergic agonists [17][18][19], 2 for cannabinoids and opioids [20,21], 3 for surgical methods [22][23][24], 4 for electrical or Chinese therapies [25][26][27][28], 2 for pardoprunox [29,30], 2 for safinamide [16], 1 for catechol-O-methyltransferase (COMT) inhibitors [31], 1 for multidisciplinary team care [32], and 7 for miscellaneous therapies. Miscellaneous therapies included hydrotherapy [33,34], massage therapy [35], gym training [36], mindfulness therapy [37], vibration therapy [38], and power yoga [39] (Table 1, with further intervention details in Appendix 4).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Pain severity was reported in 8 trials using the pain subscale of the Visual Analogue Scale (VAS-P) [17,24,26,27,29,30,33,35], in 8 using section 39 of the Parkinson's Disease Questionnaire-39 [16,22,23,31,32,36,37,39], in 4 using the Likert pain scale [18,19,34,38], in 1 using the King Parkinson's Disease Pain Scale [21], in 1 using question 1.9 of the Movement Disorders Society -Unified Parkinson's Disease Rating Scale (MDS-UPDRS Q1.9) [25], in 1 using the McGill Pain Scale [20], and in 1 trial using the Daily Pain Rating Sheet [28] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, the latter study, aside from reaching negative results, raises various issues including that operating patients too early in their disease (1) poses unnecessary exposure to surgical risks for individual patients, which cannot be easily justified by the preexisting PD disability, (2) may lead to intervention on atypical cases and (3) might have negative health economic implications [64]. In fact, in this particular study, 2 of the 15 operated patients had serious adverse events (1 perioperative stroke and 1 lead infection with subsequent device removal) [63].…”
Section: Timing Of Dbs ''Early-stim'' and ''Earliest-stim''mentioning
confidence: 83%
“…Following the Early-Stim trial, there has been a further trial exploring whether DBS might be considered even sooner, i.e., before the onset of motor complications [63]. STN DBS and BMT was compared to BMT alone in very early PD patients with a mean age of 60 years and a mean disease duration of 2 years, Hoehn and Yahr stage II off medication, and without motor fluctuations or dyskinesias.…”
Section: Timing Of Dbs ''Early-stim'' and ''Earliest-stim''mentioning
confidence: 99%
“…A 2013 clinical trial called EARLYSTIM concluded that intervening a few years earlier might be beneficial 5 . The following year, a pilot study led by researchers at Vanderbilt University in Nashville, Tennessee, went further: they gave DBS to people who had been receiving medication for as little as six months 6 . Both studies provoked a backlash, partly because of the risks associated with neurosurgery, but also owing to fears that such patients might have been misdiagnosed and instead have a different, non-Parkinson's motor disorder.…”
Section: A Treatment With Potentialmentioning
confidence: 99%